University of Florida Potato Variety Trials Spotlight: 'Peter Wilcox': HS1295, rev. 2/2021 - Andrade, Mario H.M.L.; Mwatuwa, Rodrick Z.; Christensen, Christian T.; Solano, Pam; Haynes, Kathleen G.; Zotarelli, Lincoln (EDIS, 2021)
‘Peter Wilcox’ is a fresh market potato variety selected from progeny of a cross between B0810-1 and B0918-5 and tested under the pedigree B1816-5 by the United States Department of Agriculture. In 2007, ‘Peter Wilcox’ was joint relesead with the North Carolina Agricultural Research Service, the Agricultural Experiment Stations of New Jersey, Pennsylvania, Florida, and New York, and the Maine Agricultural and Forest Experiment Station. In Florida, ‘Peter Wilcox’ demonstrates good tuber characteristics and high yields. Tuber production and quality results provided in publication are from Florida Potato Variety Trials conducted at the UF/IFAS Hastings Agricultural Extension Center between 2001 and 2019.